Crawling Motility on the Host Tissue Surfaces Is Associated With the Pathogenicity of the Zoonotic Spirochete Leptospira - Xu, Jun; Koizumi, Nobuo; Nakamura, Shuichi (Frontiers in Microbiology, 2020)
Bacterial motility is crucial for many pathogenic species in the process of invasion and/or dissemination. The spirochete bacteria Leptospira spp. cause symptoms, such as hemorrhage, jaundice, and nephritis, in diverse mammals including humans. Although loss-of-motility attenuate the spirochete’s virulence, the mechanism of the motility-dependent pathogenicity is unknown. Here, focusing on that Leptospira spp. swim in liquid and crawl on solid surfaces, we investigated the spirochetal dynamics on the host tissues by infecting cultured kidney cells from various species with pathogenic and nonpathogenic leptospires. We found that, in the case of the pathogenic leptospires, a larger fraction of bacteria attached to the host cells and persistently traveled long distances using the crawling mechanism. Our results associate the kinetics and kinematic features of the spirochetal pathogens with their virulence.